Chemical Bonds: An Integration with Islamic Brotherhood Values - Mega Legi Vela; Riky Setiawan; Metha Nur Kristanti; Tiyas Agustin; Anggita Ainur Rofiana; Anisa Nur Istiqomah; Annisa Dhaifa Salsabilla; Kustomo Kustomo; Novtavia Shintya Putri (Cakrawala: Jurnal Studi Islam, 2021)
Individuals will reap enormous benefits from bonding. There are always positive aspects to take from a bond. Covalent, ionic, and metallic bonds are examples of chemical bonds. The main ideas raised in chemical bonds are strengthened by incorporating Islamic character values. The primary objective of this study was to examine all chemical bonds and incorporate them into human life, especially in accordance with Islamic brotherhood. The findings of this study reveal that each chemical bond, whether covalent, ionic, or metallic, has a meaning that is closely related to human relations as social beings in accordance with Islamic values, as revealed by a literature review. Humans as social beings are taught to always have good relations with fellow humans through covalent bonds, and through ionic bonds, they are taught to help, work together, and take care of one another. Metallic bonds, on the other hand, teach humans to share and be sincere.